Reactivating reflexivity: towards an ethical-critical model of digital education - De Ruvo, Giuseppe (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The article proposes a model of critical digital education (CDL) to address the power dynamics of digital capitalism, highlighting the limitations of current digital literacy (DL). DL, traditionally geared towards the acquisition of technical skills for work, is criticised for its abstract and ideological approach, which ignores the socio-economic context. CDL, on the other hand, integrates critical analysis of the relationship between technologies and power, overcoming the adaptive logic of DL. This approach is grounded in Paulo Freire’s critical pedagogy, which distinguishes between ‘depository’ and ‘problematising’ education. While the former conveys notions without context, the latter stimulates critical understanding, contextualising phenomena and unmasking their ideological foundations. Applied to the digital, CDL uses this perspective to deconstruct ideological narratives, such as the myth of algorithmic objectivity, and form conscious and active citizens. The article argues that CDL can act as a catalyst for a critical theory of digital capitalism, reactivating the reflexivity of subjects and fostering the construction of emancipatory utopias. In an era dominated by the myth of algorithmic objectivity and the compression of reflexive space, critical education becomes essential for rethinking the relationships between technology, society, and power.